2008
DOI: 10.2169/internalmedicine.47.1118
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability and Hypercapnia in Duchenne Muscular Dystrophy

Abstract: Objective To investigate the relationship between heart rate variability and hypercapnia. Patients and Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 18 publications
1
11
0
3
Order By: Relevance
“…Further analysis screened out five works that did not include any analysis of HRV indices. The remained 8 studies were of an empirical nature designed as a cross-sectional case control [4,11,19,20], cross-sectional [5,21], prospective case control cohort [19], and a prospective cohort [7] (Table 1). Together, the dataset comprises 549 DMD and 142 healthy participants, and covers distinct ethnic groups: Japanese [5,7,19,22], German [21], Indian [4], Italian [11], and American [20].…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further analysis screened out five works that did not include any analysis of HRV indices. The remained 8 studies were of an empirical nature designed as a cross-sectional case control [4,11,19,20], cross-sectional [5,21], prospective case control cohort [19], and a prospective cohort [7] (Table 1). Together, the dataset comprises 549 DMD and 142 healthy participants, and covers distinct ethnic groups: Japanese [5,7,19,22], German [21], Indian [4], Italian [11], and American [20].…”
Section: Study Selectionmentioning
confidence: 99%
“…The relationship between HRV and respiratory function was examined by Lanza et al [11] and Mochizuki et al [5]. The study made by lanza et al [11] showed weak correlations between forced vital capacity and HRV indices, while Mochizuki et al [5] found that HRV index [CVrr coefficient of variation of the RR interval (%)] was negatively correlated with P a CO 2 . Based on the results, the authors proposed that low HRV may indicate respiratory insufficiency in patients with DMD, since 73% of those with CVrr < 3% had hypercapnia, and 47% of them had severe hypercapnia.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent literature has found reduced HRV in DMD [21,22], and it is well known that HRV in DMD is reduced, possibly leading to cardiac [34–36] or respiratory [36–44] failure. As the computational task induces sympathetic primacy it may be applied as a tool for improvement of heart rate autonomic modulation.…”
Section: Discussionmentioning
confidence: 99%
“…Uma alta VFC é sinal de boa adaptação, caracterizando um indivíduo saudável, com mecanismos autonômicos eficientes, enquanto que, uma baixa VFC é frequentemente um indicador de adaptação anormal e insuficiente do SNA, implicando a presença de alterações fisiológicas no indivíduo (Khaled et al, 2006). Diante da importância da utilização da VFC como um marcador que reflete a atividade do SNA e como uma ferramenta clínica para avaliar e identificar comprometimentos na saúde, Katlioriene e Zabiela (2002), Mochizuki et al (2008) e Inoue et al (2009) verificaram o comportamento da VFC em pessoas com DMD assim como outros trabalhos científicos verificaram a influência de estímulos externos na VFC, como estímulo auditivo, apresentado por Valenti et al (2013), bem como estímulo visual (Chang & Huang, 2012), ambiente líquido (Kiviniemi et al, 2012;Christoforidi et al, 2012), ambiente de estresse (BaevskiÄ­ et al, 2012), mudança de temperatura (Zaproudina et al, 2011). No entanto, apesar de sua importância estabelecida, não foram encontrados trabalhos que verifiquem o comportamento da VFC de pessoas com DMD durante tarefas cotidianas, como em utilização de computador.…”
Section: Introductionunclassified